Value co-creation in hospitality industry: A systematic literature review - Islam, R.; Loureiro, S. M. C.; Carvalho, I. (Revista Turismo e Desenvolvimento/Journal of Tourism and Development, 2023)
Service dominant (S-D) logic, which advocates prominence of services rather than goods in economic exchange, has become one of most the popular research streams in recent years. One of the most prominent theories of (S-D) logic is value co-creation. Although co-creation is mutually beneficial, it is considered to be customer-oriented and interactional. In a dynamic and interactive industry like the hotel industry, the creation of value through interaction and engagement with customers is significant to enhance business performance. This article reports a systematic literature review (SLR) to critically analyse the key findings of the publications in the domain of value co-creation related to the hospitality industry. This article also endeavours to identify and critically analyse the key themes, theories, and constructs of prior studies. The findings show that the interactive co-creative experience is significant to create positive emotion and satisfaction for hotel guests. This positive emotion and satisfaction encourage the guests to come back to the hotel and recommend it to others. Interactional co-creation also leads to more engagement, which has been found to have a significant effect on hotel performance. Therefore, hotel management should invest time and money to train and encourage hotel employees to accelerate interaction and engagement with guests to create better experience for hotel guests. This should enhance hotel performance.